Wastewater Discharge through a Stream into a Mediterranean Ramsar Wetland: Evaluation and Proposal of a Nature-Based Treatment System - De los Ríos-Mérida, Jesús; Guerrero, Francisco; Arijo-Andrade, Salvador; Muñoz, María; Álvarez-Manzaneda, Inmaculada; García-Márquez, Jorge; Bautista-Bueno, Begoña; Rendón Martos, Manuel; Reul, Andreas (MDPI, 2021)
Impacts on wetlands are becoming more pressing every day. Among them, habitat loss, overexploitation of aquifers and changes in land use are considered the most important. However, the impacts linked to wastewater discharges are increasing worldwide. In this context, this study analyses the impacts of input of wastewater to a Mediterranean Ramsar temporary wetland (Fuente de Piedra, south of Spain). To this end, systematic sampling was carried out in the Charcón stream which receives water from a wastewater treatment plant (WWTP) and discharges it into the wetland. The results showed a slight decrease in the nutrient concentrations, particularly for nitrogen compounds. Heterotrophic and fecal bacteria concentration, as well as phytoplankton and zooplankton abundance and biomass, all significantly decreased from the treatment plant to the wetland. When comparing the effect of this discharge with other similar occurring to the same wetland, it was evident that the Charcón stream was responsible for a greater impact. At this point, it is relevant to note that the main difference among both treated wastewater discharges lies in the different water retention time once the wastewater was released from the WWTP. In fact, we recommend an increase in the water retention time by building seminatural ponds, together with the use of biofilters, which will notably contribute to improve the processes of assimilation of nutrients and to decrease the impact generated in the wetland by this spill.
Keywords: Agua - Calidad; Cultural eutrophication; Management; Seminatural ponds; Temporary wetlands; Wastewater; Water quality